Goal-dependent dissociation of visual and prefrontal cortices during working memory - Lee, Sue-Hyun; Kravitz, Dwight J; Baker, Chris I (Nature neuroscience, 2013)
The authors report that, when subjects are asked to remember visual properties of an object, object identity can be decoded from fMRI measures of activity in extrastriate, but not prefrontal, cortex, whereas the opposite holds when they are asked to remember nonvisual properties. Thus, the ability to maintain information during working memory is a general and flexible cortical property. To determine the specific contribution of brain regions to working memory, human participants performed two distinct tasks on the same visually presented objects. During the maintenance of visual properties, object identity could be decoded from extrastriate, but not prefrontal, cortex, whereas the opposite held for nonvisual properties. Thus, the ability to maintain information during working memory is a general and flexible cortical property, with the role of individual regions being goal-dependent.